2010
DOI: 10.1213/ane.0b013e3181da92e4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive End-Expiratory Pressure on Internal Jugular Vein Cross-Sectional Area in Anesthetized Adults

Abstract: We tested whether positive end-expiratory pressure (PEEP) increases right internal jugular vein (RIJV) cross-sectional area (CSA) in 45 ASA physical status I and II adults. All patients received a standardized IV fluid bolus, induction of general anesthesia, tracheal intubation, and mechanical ventilation. We evaluated the CSA of the RIJV using ultrasound without PEEP (control) and with PEEP (10 cm H(2)O) in the supine, level position. Addition of PEEP increased RIJV CSA 0.42 + or - 0.41 cm(2) (mean + or - SD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…In one-third of patients PEEP of 5 cm H 2 O can increase CSA by 15.9% and PEEP of 10 cm H 2 O can increase CSA by 22% to 41%. 1,7 Trendelenburg position with 10 to 15 tilt is effective in increasing CSA of the jugular veins, a result that has been demonstrated consistently. 1,3,6,7 However, in patients with higher body mass index, clinically significant increase of the IJV CSA has not been observed with any maneuver.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In one-third of patients PEEP of 5 cm H 2 O can increase CSA by 15.9% and PEEP of 10 cm H 2 O can increase CSA by 22% to 41%. 1,7 Trendelenburg position with 10 to 15 tilt is effective in increasing CSA of the jugular veins, a result that has been demonstrated consistently. 1,3,6,7 However, in patients with higher body mass index, clinically significant increase of the IJV CSA has not been observed with any maneuver.…”
Section: Discussionmentioning
confidence: 62%
“…1,7 Trendelenburg position with 10 to 15 tilt is effective in increasing CSA of the jugular veins, a result that has been demonstrated consistently. 1,3,6,7 However, in patients with higher body mass index, clinically significant increase of the IJV CSA has not been observed with any maneuver. 1 Investigators demonstrated achievement of clinically significant increase of > 20% of the CSA in conjunction with Trendelenburg position (39% without PEEP, 52% with PEEP of 5 cm H 2 O, and 68% with PEEP of 10 cm H 2 O).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Hollenbeck et al [10] achieved an increase in RIJV cross-sectional area (CSA) by applying a positive-end expiratory pressure (PEEP) of 10 cmH 2 O in patients under general anesthesia, while Marcus et al [11] studied the degree of increase in RIJV CSA following the application of 5 and 10 cmH 2 O PEEP, with or without 20° of Trendelendburg tilting. These studies measured the RIJV CSA at its largest, without considering changes in CSA according to the respiratory cycle.…”
Section: Introductionmentioning
confidence: 99%
“…These include head rotation [4], head-down tilt [5], Valsalva maneuver [6], humming [7], Trendelenburg tilt [8], abdominal compression [9], and passive leg elevation [10]. Positive end-expiratory pressure increases IJV cross-sectional area [11]. There has been no study of the effect of elevation, and there is scant guidance on how to minimize overlapping of arteries.…”
Section: Introductionmentioning
confidence: 99%